FACTORS AFFECTING THE REGIONAL ORIGINAL INCOME OF SELAYAR ISLANDS REGENCY, SOUTH SULAWESI PROVINCE - Alwati, Alwati; Naidah, Naidah; Adziem, Faidzul (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This researcher aims to find out lokal government expenditure. gross regional, domestic product and total population influence the original regional income of selayar island regency. the type of research used in this study is quantitative. the processed data is secondary data obtanined from the regional original revenue agency, selayar island regency. the results of the data obtained from the original regional revenue agency of selayar island regency were tested for classical assumptions which consisted of outocorealisation test, multicolinerarty test, detoxification test and normality test. the data analysis method used is multiple linear regression techinques with the help of SPPS 21. the results showed that local government expenditure, gross regional, domestic produtc, the number of residents have a positive offect on the orginal income of the selayar archipelago. thus the hypothesis propesed in this study was received.